Buffering of Physiological and Affective Reactivity By a Single Proactive 5-Minute Stress Management Technique - (:unkn) unknown (My University, 2019)
A plethora of recent research highlights the long-term chronic disease risks of elevated blood pressure (BP), heart rate (HR) and affective and cognitive responses to mental stressors and how traditional forms of mindfulness meditation (MM) and progressive muscle relaxation (PMR) may help offset these long-term risks. On top of that, briefer forms of MM (e.g., 3-day training sessions) have shown benefits for emotional and physical health. Further, perseverative cognitions, or the tendency to worry and rumination about stressful events, is linked with heightened CV reactivity, and may impede the success of stress management techniques. The purpose of this study was to investigate the feasibility of using a single, 5-minute session of mindfulness meditation to reduce physiological reactivity and acute psychological mood and stress responses to a stressor (compared to an alternative stress management technique and an active control condition). We conducted the following experimental protocol: 1) collected 10-minute baseline measures of BP and HR, as well as mood and perceived stress, 2) conducted a single 5-minute stress reduction technique (MM or PMR) or control, 3) ran a short version of the Trier Social Stress Test, 4) collect mood and perceived stress measures, and 5) conducted a 10-minute recovery period to allow participants’ BP and HR levels to return to baseline. We hypothesized that (1) those in the stress management groups would show less BP and HR reactivity during the stress induction, as well as increased positive affect and/or decreased negative affect and reduced perceived stress after the stress induction compared to the control group and (2) this benefit would be greater for those who score low (vs. high) on trait PCs. Statistical analyses included mixed design repeated-measures ANOVA to assess the relationships of intervention type (MM vs PMR vs control) and period (mean BP or HR scores at each time point) with repeats on the period variable. There were no significant findings for MM or PMR reducing reactivity, perceived stress, or negative mood (nor increases in positive mood) to the stressor.
Keywords: Mindfulness Meditation; Physiological Reactivity; Progressive Muscle Relaxation; Stress; Stress Management